2018
DOI: 10.15171/bi.2018.25
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer vaccination comes to age: impacts of bioinformatics

Abstract: Introduction: Breast cancer, as one of the major causes of cancer death among women, is the central focus of this study. The recent advances in the development and application of computational tools and bioinformatics in the field of immunotherapy of malignancies such as breast cancer have emerged the new dominion of immunoinformatics, and therefore, next generation of immunomedicines . Methods: Having reviewed the most recent works on the applications of computational tools, we provide comprehensive insights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…With the advancement in massive parallel sequencing technologies, which have now generated numerous RNA-seq datasets of multiple tumor types, bioinformatic techniques that allow analysis of these powerful datasets are becoming increasingly necessary [73]. HERV-K proviruses pose a difficult challenge for computational analysis of RNA-seq data as these regions are poorly annotated and constitute repeat elements making unique alignment of RNA-seq reads difficult [49].…”
Section: Importance Of Rna-seq Analysis Pipelines For Herv-k Expression and Its Limitationsmentioning
confidence: 99%
“…With the advancement in massive parallel sequencing technologies, which have now generated numerous RNA-seq datasets of multiple tumor types, bioinformatic techniques that allow analysis of these powerful datasets are becoming increasingly necessary [73]. HERV-K proviruses pose a difficult challenge for computational analysis of RNA-seq data as these regions are poorly annotated and constitute repeat elements making unique alignment of RNA-seq reads difficult [49].…”
Section: Importance Of Rna-seq Analysis Pipelines For Herv-k Expression and Its Limitationsmentioning
confidence: 99%
“…Breast cancer is the most commonly diagnosed type of cancer in women, with its incidence ranking the highest among all malignancies ( 27 ). Accumulating evidence has demonstrated that targeted therapies offer superior therapeutic efficacy compared with conventional approaches ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here the tumor cell lysates from a patient's own tumor antigens are exploited to develop an effective immune response. However, the major disadvantages of allogeneic tumor cell vaccine (ATCV) is the inherent poor immunogenicity of tumor cells and inconsistency of the production method (Parvizpour et al 2018). In addition, due to the presence of endogenous cellular antigens, an autoimmune reaction is possible (Al-Awadhi et al 2018;Kurtz et al 2014).…”
Section: Autologous Tumor Cell Vaccinesmentioning
confidence: 99%